Pembelajaran Seru dan Interaktif melalui Pemanfaatan Media Digital Wayground pada Siswa SD Negeri 32 Oku - Wahyudi, Eka; Ningsih, Sulia; Pratama, Refaldi; Ermawati, Anggun; Jaariyah, Ainun (Pakis Journal Institute, 2026)
This Community Service Program (KKN) aims to increase student interactivity and motivation through the use of Wayground digital media for students at SDN 32, Batumarta 1 Village, Ogan Komering Ulu Regency. The partner's challenge was the limited use of digital-based learning media, resulting in a monotonous learning process that discouraged active student participation. The program's implementation consisted of several stages, including observing learning conditions, outreach to the school, educating students about the use of digital media, and providing hands-on practice using Wayground in the classroom. The results of the program demonstrated increased student enthusiasm, active participation, and motivation throughout the learning process. The use of Wayground digital media has been proven to create a more enjoyable, interactive, and meaningful learning environment. Therefore, this program is expected to become an alternative digital learning innovation that can be implemented sustainably at the elementary school level.